PILOT PLANT PERFORMANCE TEST OF PANEL ASSEMBLY OF SCALE UP FOR MOSS ROOFTOP GREENING MATERIAL (Sphagnum sp.) - Indraningtyas, Lathifa (Journal of Tropical Upland Resources (J. Trop. Upland Res.), 2021)
The application of green technology to minimize the negative impact of global warming is able to be done by developing greening materials. Previous research developed a greening material using moss (Sphagnum sp.) which was applied as a rooftop greening material on a laboratory scale and towards a commercial industrial scale through a scale up process. Geometric design by using a pilot plant with a scale up of panel length of 100 cm and a scale down of panel length with a size of 25 cm will be compared with a laboratory scale (panel length of 50 cm). This research aims to test a pilot plant performance of scale up panel for moss rooftop greening material (Sphagnum sp.). The research carried out by preparing of materials, assembling panels of greening moss material (Sphagnum sp.). on the rooftop, performance test of moss rooftop greening material including photosynthesis rate, and analysing data by using independent sample t-test. Result of research shows that the pilot plant performance test was different from the laboratory (control) due to photosynthesis rate with a difference of 25.333 mol/m2/s (scale up) and 6.33333 mol/m2/s (scale down). Furthermore, study of kinematic and dinamic similarity due to panel assembly is supposed to be done